Salt Processing Industry As A Potential For Educational Tourism In Salt Village - Damiasih, Damiasih; Ardiansyah, Putra (Sadar Wisata: Jurnal Pariwisata, 2023)
This research aims to find the potential that exists in Kampung Garam Kebumen so that we can determine strategies to develop it as an educational tourist attraction. This research uses a qualitative research method with descriptive analysis which focuses on something whose object is natural, where the researcher is the key to the instrument. The research site is located in Tlogopragoto Village, Mirit, Kebumen Regency. The data collection method using accidental sampling is included in the nonprobability sampling section by collecting data through observation, interviews and documentation. Data analysis technique using the Miles and Huberman interactive analysis model which consists of data reduction, data presentation, and drawing conclusions based on SWOT analysis. The validity of the data uses data triangulation. The results of this research show that Kebumen Salt Village has the potential as an educational tourism industry that can be visited by tourists to see the process of processing salt which is consumed by people in Indonesia. This processing process is an educational tourism attraction, tourists can also practice this process. Based on the results of the SWOT analysis of the tourism industry, it can still be developed with the right marketing strategy, so that it can penetrate foreign export markets.